GREY RELATIONAL ANALYSIS FOR PRIORITIZING INSPECTION OF PIPING SYSTEM SUBJECT TO CORROSION UNDER INSULATION - OTHMAN, MUHAMMAD FAISAL (2018)
Corrosion under Insulation (CUI) in piping systems has been a major issue to oil and gas industry over the last 50 years. CUI is very difficult to detect as the corrosion occur deeply under a covered insulation and its can be discovered until the pipe insulation has been removed or failures have occurred. Therefore, Risk Based Inspection (RBI) has been developed by American Petroleum Institute (API) to overcome CUI problem in piping system. The issue of this API method is that, the prioritization inspection for CUI is only based on the corrosion rate of the pipes without considering other factors like pipe diameter, schedule and etc. This unclear information may lead to prioritizing the wrong piping system for inspection. Thus, a new method is proposed by using Grey Relational Analysis (GRA) to prioritizing piping system. Since there are many uncertainty in piping system, GRA is one of the method for dealing with unclear information. The results obtained in this study might be differ from the actual data but the errors are less compared to API method. Hence, this paper purpose a new way of prioritizing piping system subject to CUI.